Experiential Marketing and Customer Engagement Effects on Loyalty, Mediated by Satisfaction, among 24-Hour Coffee Shop Customers in Bandar Lampung - Sabrina Ahmalina Ramadhan; Arif Sugiono; May Roni (Jurusan Akuntansi Politeknik Negeri Bandung, 2026)
In order to keep customers loyal, coffee shop owners are being forced to provide meaningful experiences due to the increasingly intense competition. Customer satisfaction assumes the role for a mediating variable; this paper seeks to examine the academic repercussions of experiential marketing and customer engagement regarding customer loyalty at Katama Coffee & Space in Bandar Lampung. The study's objectives used a quantitative methodology and utilized SEM-PLS for data analysis. A purposeful sample was utilised, collecting data from 385 respondents, and SmartPLS 4 was used for analysis. Measurement model testing, structural model testing, and direct and indirect impact hypothesis testing are all included in the analysis. The data indicate that customer satisfaction and loyalty are worthwhile, favorably enhanced by experiential marketing and customer engagement. Furthermore, improving customer satisfaction also helps to increase customer loyalty. On top of that, customer satisfaction was shown to be involved whenever an intermediate mediator facilitated exchanges about customer engagement, experiential marketing, and customer loyalty. To optimise customer experience and active involvement as a basis for establishing long-term happiness and loyalty, these findings offer insights for small coffee shops' managerial methods.